2015
DOI: 10.1186/s12906-015-0684-6
|View full text |Cite
|
Sign up to set email alerts
|

Eurythmy therapy increases specific oscillations of heart rate variability

Abstract: BackgroundMind-body therapies are beneficial for several diseases (e.g. chronic pain, arterial hypertension, mood disorders). Eurythmy therapy (EYT) is a mind-body therapy from Anthroposophic Medicine. In each EYT exercise a short sequence of body movements and simultaneous guided imagery is repeated several times. In this study, the simultaneous effects of two different EYT exercises on cardiac autonomic regulation as assessed by spectral analysis of heart rate variability (HRV) were investigated.MethodsTwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
1
11
2
Order By: Relevance
“…Both breathing and exercises are known to affect the HRV, the cardiovascular ANS marker, in somewhat of a different and varied way [32,35,37]. After our SAR combined and integrated exercise session, the directions of the change of the other HRV parameters were increase in LF, almost no change in HF, increase in LF/HF, and a mild increase in SDNN.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Both breathing and exercises are known to affect the HRV, the cardiovascular ANS marker, in somewhat of a different and varied way [32,35,37]. After our SAR combined and integrated exercise session, the directions of the change of the other HRV parameters were increase in LF, almost no change in HF, increase in LF/HF, and a mild increase in SDNN.…”
Section: Discussionmentioning
confidence: 83%
“…The HF is generally considered as representing parasympathetic activity and vagal activation, and is associated with more relaxed state. The LF is reflective of both sympathetic and parasympathetic activities to be associated with baroreflex sensitivity [32,35].…”
Section: Discussionmentioning
confidence: 99%
“…Therapies with body movement provide a better regulation and modulation of heartbeats and may vary according to the frequency of these activities and types of movements. This is evidenced in studies that have identified that oscillations of the HRV increase during Eurythmy therapy, mainly elevation of the parasympathetic stimulation, resulting from a better adaptation of the ANS and vagal control on bodily movements stimulation 20 .…”
Section: Discussionmentioning
confidence: 95%
“…Results obtained in [112] show that an anthroposophic therapy can be beneficial to several conditions, such as chronic pain, hypertension and mood disorders, with an impact on HRV (see Figure 5). Biofeedback therapy is a trans-disciplinary intervention method for chronic pain [113].…”
Section: Pain Therapies and Hrvmentioning
confidence: 99%